Cognitive Development Trajectories in Preterm Children With Very Low Birth Weight Longitudinally Followed Until 11 Years of Age - Stålnacke, Sofia Ryytty; Tessma, Mesfin; Böhm, Birgitta; Herlenius, Eric (Frontiers in Physiology, 2019)
Background: There is a high prevalence of cognitive dysfunction in very low birthweight (500-1250 g) infants (VLBW). Understanding long-term risk factors associated with cognitive development in preterm children requires longitudinal characterization. Thus, follow-up evaluations– including identification of risks and resilience influences–are important to promote health and cognitive abilities of children born preterm. Aim: To examine changes in cognitive development from birth until 11 years of age in preterm children with very low birthweight. Method: 24 VLBW infants, at the Karolinska University Hospital, Stockholm, were assessed with regards to cognitive functioning at three times during development (18 months, 5 years and 11 years of age using standardized tests. Longitudinal data were analyzed using Generalized Estimating Equation (GEE) univariate and multivariate models. Results: The follow-up rate was 100%. Level of cognitive functioning at 18 months and at 11 years was similar. Females had higher cognitive scores than males at all three timepoints. We found that intraventricular hemorrhage (IVH) and prolonged invasive ventilatory support (> 7days) had a negative effect on cognitive functioning. Higher levels of parental education had a favorable influence on cognitive functioning over time. Conclusion: Level of cognitive development at 18 months was highly predictive for level of cognitive function at 11 years of age and differences in assessment scores between male and female VLBW infants persisted. Additional longitudinal studies, performed before school entry and across childhood, are needed to further elucidate the cognitive trajectories of preterm children